Pekanbaru Youth Center Dengan Pendekatan Arsitektur Dekonstruksi - Lestari, Riska; Aldy, Pedia; Hidayat, Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The ethuasiasm of adolescents in Pekanbaru to development of the arts, entertainment, sports, education, and recreation is quite large. This is done by their desire to create and angage these fields to relieve stress and return after their activities. The pattern of social interaction with teenegers being joined with ‘community’. But unfortunately the potential and achievement of adoloscents in the community is not supported by the availability of space and the masses in accordance with activity needs. Taking the location of design at Jl. Naga Sakti, Pekanbaru Youth Center is present as a solution of activity and interaction of adolescent with Decontruction Architecture as paradigm and applying four of Daniel Libeskinds design methods namely Metaphora, Fragmentation, Void, dan Disorientation. The final result is the creation of a container that can accommodate and distribute their interests and talents, so they can be active and increase their social value.Keyword : Adolescent, Community, Decontruction Architecture, Youth Center